Curcuma (Curcuma xanthorrhiza Roxb) diseases in different composition of fertilizer - Arlyna B Pustika; Fibrianty Fibrianty; Retno Utami Hatmi (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2012)
Curcuma or Java Turmeric as traditional medicine has given significant contribution in industrial empowerment. The demand increased, following the increase of food and drink industry based on curcuma. Therefore, extensification and intensification in curcuma cultivation was developed, included variety and fertilizer composition. Combination of chemical and organic fertilizer was used to increase the yield. However, the effect of fertilizer to plant disease intensity should be determined. Based on the observation at month 6th, the dominant diseases were Fusarium wilt, leaf spots caused by Phyllosticta sp., Colletotrichum sp. and Gloeosporium sp. The greatest percentage of Fusarium wilt (11.11%) was found in variety Cursina 1 that received organic fertilizer 10 ton/ha, with disease intensity 60.52%; whilst the lowest percentage (0%) was found in Cursina 2 that received organic fertilizer. The greatest percentage of leaf spot was seen in Cursina 2 that was given organic fertilizer, with disease intensity 41.67%; whilst the lowest percentage was found in Cursina 1 that received the combination of organic fertilizer 10 ton/ha, 100 kg/ha urea, 100 kg/ha KCl, and 100 kg/ha SP-36, with disease intensity 18.06%.Keywords: curcuma, disease, fertilizer